The Amazon biome in messages - Tucci, Giulia; Silveira Carneiro, Bia; Ruscica, Giosue (2025)
This project aims to investigate how debates concerning the Amazon Rainforest are framed and disseminated within public Telegram channels in English, Portuguese, and Spanish. The research seeks to identify and analyze prevailing narratives, thematic focuses, and patterns of information exchange within these multilingual online discussions.